Implementasi Kendali Palang Pintu Kereta Api Menggunakan IR Sensor dan NRF24L01 - Bagus Priyo Pangestu; Barlian Henryranu Prasetio; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Crossings train is a cross where meetings of railway line with the way , the highway or a trail other. In indonesia , many cases accident in the area were caused lack of keys no have facilities cross bar train , hence often to cause casualties .In addition , there are also some cases accident on an area of crossings train because the factors human error like road users lacking in discipline or guard at the cross bar that causes inactive of cross bar as its function .To reduce factors accident above , so designed a system control cross bar train automatically with combined some ir censors or censor infrareds as count vehicles and read the speed of a train. Based two of the input , so produced a decision of output the movement of cross. The movement of the decision cross arranged using fuzzy logic sugeno which will produce cross movement move quickly , medium or slowly. For communication the submission of the data in wireless using module nrf24l01. Into execution of the entire program when run , 9971 been gained up to cross 10071 milisecond will close fast , 13031 up to cross 13080 milisecond will close medium and 22461 up to cross 22571 milisecond will close slowly with delivery performance data is wireless 460 up to 580 milisecond by inference a system of working to fit as desired with the execution of the program in do a decision less than a time limit set 61.2 seconds that is the train travel time prior to the the crossing gate railway with the top speed of 60 km per hour with error ratio 4.6 % between system time and realtime.